La entonación de las interrogativas absolutas no marcadas en el español boricua: ¿un patrón descendente o circunflejo? - Baditzné Pálvölgyi, Kata (Acta Hispanica, 2017)
The present investigation focuses on the intonation of unmarked Puerto Rican yes-no questions. Puerto Rico belongs to the Caribbean dialectal zone from an intonational point of view, hence this type of questions is accompanied by a final descendent melodic movement, which is untypical in the rest of the Spanish speaking world. By the help of 51 Puerto Rican utterances taken from spontaneous speech Youtube videos, we will examine if the characteristic falling pattern of this type of sentences is a circumflex one starting from the last accented syllable, or a rising one followed by a fall starting from the last accent. In addition, it is also our aim to determine the percentage of the final fall.